Triisopropylsilylethynyl‐Functionalized Graphene‐Like Fragment Semiconductors: Synthesis, Crystal Packing, and Density Functional Theory Calculations. Issue 52 (25th November 2013) - Zhang, Lei; Fonari, Alexandr; Zhang, Yue; Zhao, Guangyao; Coropceanu, Veaceslav; Hu, Wenping; Parkin, Sean; Brédas, Jean‐Luc; Briseno, Alejandro L.
Abstract Tri‐isopropylsilylethynyl (TIPS)‐functionalized polycyclic aromatic hydrocarbon (PAH) molecules incorporate structural components of graphene nanoribbons and represent a family of model molecules that form organic crystal semiconductors for electronic devices. Here, we report a series of TIPS‐functionalized PAHs and discuss their electronic properties and crystal packing features. We observe that these soluble compounds easily form one‐dimensional (1 D) packing arrangements and allow a direct evolution of the π stacking by varying the geometric shape. We find that the aspect ratio between length and width plays an important role on crystal packing. Our result indicates that when the PAH molecules have zigzag edges, these can provide enough volume for the molecules to rotate and reorient, alleviating the unfavorable electrostatic interactions found in perfectly cofacial π–π stacking. Density functional theory calculations were carried out to provide insights into how the molecular geometric shape influences the electronic structure and transport properties. The calculations indicate that, among the compounds studied here, "brick‐layer" stacks provide the highest hole mobility.